2022
DOI: 10.1002/open.202200142
|View full text |Cite
|
Sign up to set email alerts
|

Front Cover: (ChemistryOpen 7/2022)

Abstract: The Front Cover shows a core‐substituted naphthalene diimide with dimethylamine (DDPT) groups which has been used as a reversible acid‐base sensor. The color‐changing tides of the sea represent the acid‐base‐mediated colorimetric changes the DDPT probe exhibits, switching from blue to violet. DDPT could be an efficient alternative to overcome the irreversibility of commonly used pH paper, as it also works when immobilized on paper. More information can be found in the Research Article Vishal G. More et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Various probes were designed and reported that exhibited AIE or ACQ for pH detection with a core of benzimidazole, 16 xanthene, 17 coumarin, 18 quinoline, 19 or naphthalene diimide (NDI). 20 Among AIE-active molecules, tetraphenylethylene (TPE) exhibited AIE as well as ACQ phenomena, depending on the receptor attached to the periphery. By tuning such receptor sites on phenyl rings, our group has reported an AIE-active tetrapyridyl-substituted TPE (TPy-TPE) for intracellular pH detection 21 and zinc sulfate sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Various probes were designed and reported that exhibited AIE or ACQ for pH detection with a core of benzimidazole, 16 xanthene, 17 coumarin, 18 quinoline, 19 or naphthalene diimide (NDI). 20 Among AIE-active molecules, tetraphenylethylene (TPE) exhibited AIE as well as ACQ phenomena, depending on the receptor attached to the periphery. By tuning such receptor sites on phenyl rings, our group has reported an AIE-active tetrapyridyl-substituted TPE (TPy-TPE) for intracellular pH detection 21 and zinc sulfate sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, NDI has been more explored in the sensing of anions, cations, pH, biosensors, etc. 25,26 Herein, we have reported NDI core-based simple and efficient molecular probe 1, prepared in several steps starting from NDA 2, for the selective and sensitive detection of CN − ions, as shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%